2010
DOI: 10.1080/17415993.2010.493199
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of sulfur on mercury capture from coal-fired utility flue gases

Abstract: Coal combustion continues to be a major source of energy throughout the world and is the leading contributor to anthropogenic mercury emissions. Effective control of these emissions requires a good understanding of how other flue gas constituents such as sulfur dioxide (SO 2 ) and sulfur trioxide (SO 3 ) may interfere in the removal process. Most of the current literature suggests that SO 2 hinders elemental mercury (Hg 0 ) oxidation by scavenging oxidizing species such as chlorine (Cl 2 ) and reduces the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…O 2 improves mercury retention [20,23] whereas reactive gases such as SO x and NO x may modify the surface of the carbons and favor or inhibit mercury adsorption [24][25][26][27]. Other gases such as H 2 O may also play an important role in the mechanism of Hg adsorption on the surface of the activated carbon [20,[28][29][30], and it has also been suggested that CO 2 might compete with Hg for the same adsorption sites [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O 2 improves mercury retention [20,23] whereas reactive gases such as SO x and NO x may modify the surface of the carbons and favor or inhibit mercury adsorption [24][25][26][27]. Other gases such as H 2 O may also play an important role in the mechanism of Hg adsorption on the surface of the activated carbon [20,[28][29][30], and it has also been suggested that CO 2 might compete with Hg for the same adsorption sites [22].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the study of the mechanism of mercury capture on activated carbon is based not only on the interactions between mercury and carbon but also on the competitive reactions of these gases with the solid. Special attention has been paid to the role of SO x and the formation of sulfuric acid (H 2 SO 4 ) [22,[24][25][26][27] which may condensate on the carbon surface in different amounts preventing the adsorption of Hg 0 or favoring the reaction with mercury to form Hg 2 SO 4 [20]. Most of the knowledge acquired until now on Hg-activated carbon interactions has been obtained from studies carried out in atmospheres typical of coal combustion in air but there is a lack of similar knowledge on the interactions of Hg-activated carbons in oxy-combustion atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data on this aspect were not available, but these values are particularly important if sulphur is to be sold as a by-product and not treated as a waste. The capacity of sulphur to retain gaseous Hg has to be related to the proportions of Hg, S and Cl in the raw materials [22]. Daily evolution trends were not significantly different for these solid waste and byproduct streams, except for sulphur, which showed a decreasing trend that mirrored the raw materials trend.…”
Section: Solid Streams: Wastes and By-productsmentioning
confidence: 96%
“…According to previous results by the authors and other researchers [33][34] a higher proportion of oxidation of SO 2 to SO 3 occurs during oxycombustion than in air combustion. After several investigations into the role of SO 2 /SO 3 in mercury retention by activated carbons [35][36][37][38][39] it was concluded [12] that SO 3 in flue gases can cause the formation of H 2 SO 4 on the activated carbon surface, which would enhance Hg 0 adsorption. However, in the present study SO 3 and/or H 2 SO 4 might not be favoring Hg capture in the oxy-combustion atmosphere due to the slow kinetics of the reaction [12] where the activated carbon-gas contact time is lower than 1 second, similar to the contact time when activated carbon is injected into a coal-fired power plant.…”
Section: Mercury Retention Capacitymentioning
confidence: 99%